Table of Contents (Law, State and Telecommunications Review, 2020)
Dear Reader, We are pleased to introduce the first issue of the twelfth volume of the Law, State and Telecommunications Review (LSTR).In this issue, the journal published a number of original articles on topics relevant to ICT and telecommunications from an interdisciplinary perspective.We are delighted to include articles on vertical integration in the audiovisual industry in Brazil, must-carry and retransmission consent regulation in the U.S.A., France and Mexico, privacy in social networks, artificial intelligence applied to judicial resolution of conflicts, right to access digital platforms, the Chilean case of policy to close the digital gap, civil responsibility of the Internet giants, radiofrequency market in Brazil, technical improvements to wireless sensor networks, personal data protection and big data, analysis of the de-indexing procedure of Google Adwords, and electronic documents workflow regulation in post-Soviet countries, in North America and in Europe.For future issues, we will continue to publish articles on all relevant areas of ICT and telecommunications.We hope you have enjoyed reading this issue looking forward to a second issue of the twelfth volume to be released on October 2020. Sincerely, Prof. Marcio Iorio AranhaEditor-in-Chief, The Law, State and Telecommunications ReviewOn behalf of the Editorial Board